Factors influencing support for cultural tourism development: Community attachment, social-psychological and cultural attitudes - Çelik, Sedat; Coşkun, Erhan; Yıldız, Nevzat (Turyzm/Tourism, 2026)
The local community has different attitudes towards the economic, environmental and socio-cultural impacts of tourism. However, studies examining the relationships between attitudes towards tourism development and social psychology, cultural attitudes and community attachment, are limited. In this context, the aim is to investigate the impact of social-psychological and cultural attitudes as well as community commitment to support for cultural tourism development. A quantitative research method has been applied and data were obtained from participants, determined by convenience sampling, with a questionnaire technique. The surveys were conducted among the local residents of Cizre district in Şırnak province, located in the south-east of Türkiye. Descriptive statistics, factor, correlation and regression analyses were used to explain the conceptual model. The results of the research show that community commitment, cultural attitude and the social-psychological attitudes of local people positively affect the development of cultural tourism. In the light of the research results, various recommendations are presented.